A case of ectopic hepatocellular carcinoma around the common bile duct in a dog - OKADERA, Ryota; OSUGA, Tatsuyuki; HIRAI, Takuya; KONNO, Ryusei; TANABE, Mika; FUKE, Naoyuki; SAITO, Eren; KANEKO, Yasuyuki; NAGANOBU, Kiyokazu (Journal of Veterinary Medical Science, 2025)
A 10-year-old, male neutered pug dog with a history of gallstones was found to have a mass near the caudate lobe of the liver upon ultrasound examination. The mass was red to dark red, multinodular, measuring 3 × 3 × 4 cm and not continuous to the liver. Histopathological examination revealed sheet-like proliferation of polygonal neoplastic cells resembling hepatocytes with mild atypia, and no portal areas were observed. The tumor cells were positive for HepPar-1 and negative for cytokeratin 7. The macrophages decreased in neoplastic lesion compared to normal area. Based on these findings, this case was diagnosed as a hepatocellular carcinoma of ectopic liver origin. This is the second reported case showing the potential for ectopic liver to develop into tumors in dogs.